P6 Developing DNACPR simulation sessions for senior doctors. (3rd November 2019) - Preston, Harriet; Hatch, Mark; Walker, Anne-Marie
Abstract : Background: Do Not Attempt Cardiopulmonary Resuscitation (DNACPR) discussions and decisions form an integral part of advance care planning. Although DNACPR is a medical decision, doctors have a legal duty to involve patients and relatives. However such conversations can be difficult, requiring good communication skills and an understanding of the legal position. We recognised a lack of training and clarity regarding DNACPR and the law amongst physicians and looked at ways to bridge this gap. Summary of work: Simulation has been well recognised as an effective method to teach communication skills. 1 The aim was to develop a simulation-based education session for senior doctors, to clarify the legal position regarding DNACPR and to give them an opportunity to practise discussions in a safe, supported environment. The sessions were developed following a successful bid for network Multi-Professional Education and Training funding. 5–8 candidates participate in a 3 hour session. A pre-briefing clarifies the legalities around DNACPR. Each session comprises 3 bespoke scenarios using patient actors, with candidates playing the part of the doctor. Video-playback is used to assist the debrief process. As a result of the success of the initial programme the training has been rolled out to a first cohort of 13 senior community nursing staff who have completed advanced communication skills training. Summary of Results: Since 2015, 21 sessions have taken place with a total of 85 attendees, including a wide range of medical and nursing staff. Evaluation has been extremely positive. 99% of candidates agreed or strongly agreed that they felt more confident about the legal position regarding DNACPR. 70% strongly agreed that they felt more confident undertaking DNACPR discussions with patients and relatives and 89% strongly agreed that they would recommend the course to colleagues. Qualitative feedback includes comments such as 'Excellent! 'should be mandatory' and 'everyone should do this.' Feedback from the intial nursing cohort was also overwhelmingly positive and following their training all have held DNACPR conversations with patients and completed DNACPR forms. Discussion, conclusions and recommendations: Having a dedicated simulation centre at the trust has been invaluable. The main challenge has been encouraging attendance and several sessions have been cancelled because of lack of candidates. We are currently exploring the feasibility for the program to become part of mandatory training. Following the successful roll out to community nursing staff we will be looking at extending the training to nursing staff within the acute trust. References: Blackmore A, Kasfiki EV, Purva M. Simulation-based education to improve communication skills: a systematic review and identification of current best practice. BMJ Simulation and Technology Enhanced Learning 2018; 4:159–164.